Usefulness of novel martin/hopkins and sampson equations over friedewald equation in cardiology outpatient: CVSCORE-TR substudy. (11th May 2021) - Dinc Asarcikli, L; Kis, M; Guvenc, T; Tosun, V; Acar, B; Avci Demir, F; Naser, A; Zoghi, M; Keles, F; Usalp, S; Aslanturk, OF; Uygun, T; et al.
Abstract: Funding Acknowledgements: Type of funding sources: None. OnBehalf: CVSCORE-TR study group Background: Friedewald equation (LDL-Cf) is known to produce inaccurate estimations of low-density lipoprotein cholesterol (LDL-C) when triglycerides are high (>400 mg/dl) or LDL-C is low (<70 mg/dl). Martin/Hopkins (LDL-Cmh) and Sampson (LDL-Cs) equations were developed to overcome these limitations, but few data are available whether these equations offer incremental usefulness over LDL-Cf. Purpose: In this pragmatic study, we aimed to evaluate the agreement between LDL-C calculated using LDL-Cmh, LDL-Cs and LDL-Cf equations and to understand whether using LDL-Cmh or LDL-Cs instead of LDL-Cf leads to significant changes on the clinical decision-making Methods: 4196 cardiology outpatient cases that were included in a multicenter registry database were analyzed. Each case was assigned into a cardiovascular risk class using web-based SCORE (Systematic COronary Risk Evaluation) algorithm calibrated for high-risk European countries, and relevant European guidelines were used to assess LDL-C targets. LDL-Cf, LDL-Cs and LDL-Cmh were calculated as previously described. Results: Compared to LDL-Cmh and LDL-Cs, LDL-Cf was able to correctly identify 96.9%-98.08% of cases as within or out of LDL-C target, respectively, while 1.95%-2.8% of cases were falsely identified as within LDL-C target. Kappa coefficients for agreement between LDL-Cf vs. LDL-Cmh and LDL-Cf vs. LDL-Cs were 0.868 and 0.918 (p < 0.001 for both). For patients not on anticholesterolemic drugs, decision to initiate treatment would be different in 1.2%-1.8% of cases if LDL-Cs or LDL-Cmh were used, respectively. For those already on anticholesterolemic drugs, decisions regarding to treatment intensification would be different in 1.5%-2.4% of cases if LDL-Cs or LDL-Cmh were used. Conclusions: Friedewald equation had an excellent degree of agreement with the novel Martin/Hopkins and Sampson formulas in most cardiology outpatients, especially those within the lower end of the cardiovascular risk spectrum. In selected patients, especially those with high or very high risk in whom LDL-Cf < 70 mg/dl or those with a TG > 400 mg/dl, agreement was far worse and thus novel equations might have an incremental usefulness for clinical decision making.